Fluorosilicon-modified polyurea anticorrosive coating and its preparation method
Through the composition of components A and B of fluorosilicone modified polyurea coatings, the problem of insufficient corrosion resistance in steel structures is solved, and higher corrosion resistance and mechanical properties are achieved, dense and smooth coatings are formed, and the tolerance to acids, alkalis and organic solvents is enhanced.
Patent Information
- Application Number
- CN202510490244.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-18
- Publication Date
- 2025-07-08
- Estimated Expiration
- 2045-04-18
AI Technical Summary
The existing polyurea coatings in steel structures have no performance in corrosion protection that meets the growing practical application requirements, especially in atmospheric corrosion resistance, low acid and alkaline media and inorganic salt solutions, and are prone to cracking and penetration during construction.
Fluorosilicone modified polyurea coating is used to enhance corrosion resistance by combining component A and component B. Component A is used to improve the corrosion resistance. Component B is added with N,N-dihydroxy(diisopropyl)aniline and 4,4'-methylene-bis(3-chloro-2,6-diethylaniline) and other substances to enhance the mechanical properties. The preparation method includes controlling the reaction under stirring speed and temperature conditions.
It improves the corrosion resistance, mechanical properties and permeability of the coating, forms a dense and smooth surface, reduces the surface energy, enhances the hardness and elasticity of the coating, reduces the risk of cracking, and improves the tolerance to acids, bases and organic solvents.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polyurea coating preparation, and particularly relates to a fluorosilicon-modified polyurea anticorrosive coating and a preparation method thereof. Background Art
[0002] Polyurea is a polymer material with urea bonds formed by the reaction of component A isocyanate and component R terminal amine compound. Among them, most of the component A in polyurea is isocyanate monomer or its polymer, and component R is an amine compound composed of terminal amino chain extender and terminal amino resin.
[0003] Polyurea anticorrosive coating has excellent corrosion resistance and anti-aging performance. Especially in the aspects of anti-atmospheric corrosion, low-acid and low-alkali media and inorganic salt solutions, it has excellent anticorrosion performance, and is convenient for on-site construction, has strong adhesion, the coating is not easy to crack, and has strong anti-permeability ability. It is a new type of material in the current anticorrosion field, with the characteristics of long-term effectiveness and wide applicability.
[0004] Steel structure is a structure composed of steel materials and is one of the main building structure types. Its application range is becoming more and more extensive. The steel structure is exposed to the external environment for a long time and is prone to corrosion under the influence of temperature / humidity, which will not only seriously affect its service life and safety, but also cause waste of resources and environmental pollution. Coating polyurea coating on the surface of steel structure has become the main means of steel structure anticorrosion. However, the anticorrosion performance, mechanical properties and medium resistance performance of the paint film formed by the existing polyurea coatings can no longer meet the increasing actual application requirements and cannot provide long-term protection for steel structures well.
[0005] Therefore, it is necessary to explore a new type of polyurea anticorrosive coating. Summary of the Invention
[0006] The object of the present invention is to provide a fluorosilicon-modified polyurea anticorrosive coating, and the polyurea coating has excellent corrosion resistance and mechanical properties; the present invention also provides a preparation method thereof at the same time.
[0007] The fluorosilicon-modified polyurea anticorrosive coating described in the present invention is composed of component A and component B, and the volume ratio of component A to component B is 1:1. Among them, component A is composed of the following raw materials by weight: 15-17 parts of fluorinated polysiloxane, 48-50 parts of hexamethylene diisocyanate, 21-23 parts of diphenylmethane diisocyanate, and 36-38 parts of diethylene glycol adipate; component B is composed of the following raw materials by weight: 42-44 parts of amino-terminated polyether, 15-17 parts of 4,4'-methylene-bis(3-chloro-2,6-diethylaniline), 8-10 parts of N,N-dihydroxy(diisopropyl)aniline, and 5-7 parts of 3,5-bis(trifluoromethyl)phenyl silicone oil; the preparation method of the fluorinated polysiloxane is as follows: under a nitrogen atmosphere, add tetradecamethylcycloheptasiloxane and tetraethylammonium hydroxide to a reaction vessel, and then sequentially dropwise add (3,3,3-trifluoropropyl)trimethoxysilane and diethylenetriaminepropyltrimethoxysilane. First, heat up to 70-75°C and react for 2.2 h, then heat up to 103-105°C and react for 12.5 h, and finally heat up to 153-155°C under vacuum conditions and hold for 40 min to prepare the fluorinated polysiloxane.
[0008] Among them:
[0009] During the preparation process of the fluorinated polysiloxane, the stirring speed is controlled at 500 r / min.
[0010] The molar ratio of tetradecamethylcycloheptasiloxane to (3,3,3-trifluoropropyl)trimethoxysilane is 1:0.33-0.35.
[0011] The mass of diethylenetriaminepropyltrimethoxysilane accounts for 0.6-0.8% of the mass of tetradecamethylcycloheptasiloxane.
[0012] The mass of tetraethylammonium hydroxide accounts for 0.8% of the total mass of tetradecamethylcycloheptasiloxane, (3,3,3-trifluoropropyl)trimethoxysilane, diethylenetriaminepropyltrimethoxysilane, and tetraethylammonium hydroxide.
[0013] The hydroxyl value of the diethylene glycol adipate in component A is 125 mgKOH / g, the molecular weight is 900, the manufacturer is Aolilon (Jining) Chemical Co., Ltd., and the model is XCP-900D.
[0014] The functionality of the amino-terminated polyether in component B is 2, the molecular weight is 2000, the manufacturer is Zibo Zhengda Polyurethane Co., Ltd., and the model is ZD-1200.
[0015] The preparation method of the fluorosilicon-modified polyurea anticorrosive coating described in the present invention comprises the following steps:
[0016] (1) Preparation of component A
[0017] Put hexamethylene diisocyanate and diphenylmethane diisocyanate into a reaction kettle and heat up to 83 - 85°C. Dropwise add fluorinated polysiloxane into the reaction kettle and react for 1.8 h. Then heat up to 100 - 105°C, dropwise add dehydrated polyethylene adipate glycol ester and keep the temperature for 3 h. After the reaction is completed, cool it to room temperature to prepare Component A;
[0018] (2)Preparation of Component B
[0019] Put N,N - dihydroxy(diisopropyl)aniline and 4,4'-methylene - bis(3 - chloro - 2,6 - diethylaniline) into a reaction kettle, heat up to 93 - 95°C to dissolve them, then add terminal amino polyether and 3,5 - bis(trifluoromethyl)phenyl silicone oil, stir at a rate of 400 - 500 r / min for 45 min to mix them evenly, and finally heat up to 108 - 110°C and react for 2.5 h. After the reaction is completed, cool it to room temperature under a nitrogen atmosphere to prepare Component B;
[0020] (3)Preparation of fluorosilicon - modified polyurea anticorrosive coating
[0021] During use, mix Component A and Component B according to a volume ratio of 1:1 and spray them to prepare the fluorosilicon - modified polyurea anticorrosive coating.
[0022] Among them:
[0023] The dehydrated polyethylene adipate glycol ester described in step (1) is obtained by dehydrating polyethylene adipate glycol ester at 110 - 113°C for 3 h.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] (1)For the fluorosilicon - modified polyurea anticorrosive coating of the present invention, Component A and Component B act synergistically to ensure that the prepared fluorosilicon - modified polyurea anticorrosive coating has excellent properties. In Component A, fluorinated polysiloxane and polyethylene adipate glycol ester are used in combination to improve the corrosion resistance of the polyurea coating; in Component B, in addition to adding terminal amino polyether, N,N - dihydroxy(diisopropyl)aniline, 4,4'-methylene - bis(3 - chloro - 2,6 - diethylaniline) and 3,5 - bis(trifluoromethyl)phenyl silicone oil are also added to ensure the mechanical properties of the prepared polyurea coating.
[0026] (2) In the fluorosilicon-modified polyurea anticorrosive coating of the present invention, in component A, hexamethylene diisocyanate and diphenylmethane diisocyanate are selected and used in combination. Using hexamethylene diisocyanate as the main component ensures that the prepared polyurea anticorrosive coating has a longer activation period and better weather resistance. The addition of diphenylmethane diisocyanate is beneficial to increasing the hardness of the formed coating, improving the anti-permeability of the coating, and thus enhancing the medium resistance of the coating. In addition, fluorinated polysiloxane and diethylene glycol adipate are added to component A. Diethylene glycol adipate contains carboxylate groups, which can endow the polyurea anticorrosive coating with excellent oil resistance and improve the resistance to hydrocarbon solvent erosion. At the same time, the ester groups in its molecular structure can interact with acids and alkalis to form relatively stable chemical bonds or complexes, thereby reducing the destructive effect of acids and alkalis on the coating and improving the chemical corrosion resistance of the coating. The fluorine atoms in the fluorinated polysiloxane molecule have high electronegativity and small atomic radius, which can form stable chemical bonds, making the coating more resistant to chemical media such as acids, alkalis, and salts, effectively preventing their penetration and erosion of the coating. The introduction of fluorinated polysiloxane reduces the surface energy of the coating, making it have good hydrophobicity and oleophobicity, reducing the adhesion and penetration of corrosive media on the coating surface, and thus improving the corrosion resistance of the coating. Since the addition of fluorinated polysiloxane can reduce the surface tension of the polyurea anticorrosive coating, the prepared coating can form a smoother and flatter surface during the curing process, reducing microdefects, thereby improving the denseness of the coating. In addition, the addition of both fluorinated polysiloxane and diethylene glycol adipate can increase the hardness and elasticity of the coating formed by the polyurea anticorrosive coating, making it have better anti-deformation ability and recovery ability when subjected to external forces, and reducing the coating cracking caused by stress concentration.
[0027] (3) In the preparation method of the fluorinated polysiloxane in component A of the fluorosilicon-modified polyurea anticorrosive coating of the present invention, tetradecamethylcycloheptasiloxane is used as the main raw material, diethylenetriaminepropyltrimethoxysilane is used as the amino crosslinking agent, and tetraethylammonium hydroxide is used as the basic catalyst to promote the occurrence of ring-opening reaction. At the same time, the amount of the catalyst is controlled to avoid excessive crosslinking. Fluorine groups are introduced through (3,3,3-trifluoropropyl)trimethoxysilane to enhance the hydrophobicity and oleophobicity of the prepared fluorinated polysiloxane. During the preparation, first, the hydrolysis of silane is promoted at 70 - 75 °C, and then the temperature is raised to 103 - 105 °C for condensation and ring-opening copolymerization. Since the -NH2 of diethylenetriaminepropyltrimethoxysilane preferentially condenses with the silanol, the hydrolysis product of (3,3,3-trifluoropropyl)trimethoxysilane, the introduction rate of fluorine groups is reduced. Therefore, it is necessary to strictly control the addition amount and addition method of (3,3,3-trifluoropropyl)trimethoxysilane.
[0028] (4) In the fluorosilicon-modified polyurea anticorrosive coating of the present invention, N,N-dihydroxy(diisopropyl)aniline and 4,4'-methylene-bis(3-chloro-2,6-diethylaniline) in component B are used as crosslinking and chain-extending agents. The rigid benzene ring structure, chlorine, and ethyl substituents in 4,4'-methylene-bis(3-chloro-2,6-diethylaniline) can endow the formed polyurea anticorrosive coating with higher hardness and tear resistance. N,N-dihydroxy(diisopropyl)aniline is an alcoholamine compound. The hydroxyl and amino groups in its molecular structure enhance the intermolecular force through hydrogen bonding. At the same time, its flexible chain segment can improve the impact resistance of the coating. The two work synergistically to improve the crosslinking density and mechanical properties of the coating while maintaining the flexibility and elasticity of the coating, avoiding the increase in coating brittleness caused by too high crosslinking density. In addition, the chlorine atoms and ethyl substituents in 4,4'-methylene-bis(3-chloro-2,6-diethylaniline) enhance the oil resistance, acid and alkali corrosion resistance of the coating. The hydroxyl structure of the compounded N,N-dihydroxy(diisopropyl)aniline can participate in the formation of a denser crosslinking network, reducing the moisture penetration path. Therefore, the two are compounded and used to further improve the anticorrosive performance of the prepared polyurea coating. In addition, 3,5-bis(trifluoromethyl)phenyl silicone oil is added to component B. The trifluoromethyl groups in its molecular structure endow it with strong hydrophobicity and chemical inertness. This property can enhance the tolerance of the coating formed by the prepared polyurea coating to acids, alkalis, and organic solvents, while reducing the viscosity of component B and reducing the orange peel and pinhole defects during spraying, which is beneficial to the formation of a denser seamless coating.
[0029] (5) The preparation method of the fluorosilicon-modified polyurea anticorrosive coating of the present invention has a simple process and easy-to-control parameters, making the performance of the prepared polyurea coating stable. Detailed implementation manners
[0030] The present invention will be further described below in conjunction with embodiments.
[0031] Example 1
[0032] The fluorosilicon-modified polyurea anticorrosive coating described in Example 1 is composed of Component A and Component B, and the volume ratio of Component A to Component B is 1:1. Among them, Component A is composed of the following raw materials by weight: 16 parts of fluorinated polysiloxane, 49 parts of hexamethylene diisocyanate, 22 parts of diphenylmethane diisocyanate, and 37 parts of diethylene glycol adipate; Component B is composed of the following raw materials by weight: 43 parts of amino-terminated polyether, 16 parts of 4,4'-methylene-bis(3-chloro-2,6-diethylaniline), 9 parts of N,N-dihydroxy(diisopropyl)aniline, and 6 parts of 3,5-bis(trifluoromethyl)phenyl silicone oil; the preparation method of the fluorinated polysiloxane is as follows: under a nitrogen atmosphere, add tetradecamethylcycloheptasiloxane and tetraethylammonium hydroxide to a reaction vessel, and then sequentially dropwise add (3,3,3-trifluoropropyl)trimethoxysilane and divinyltriaminopropyltrimethoxysilane. First, raise the temperature to 73 °C and react for 2.2 h, then raise the temperature to 104 °C and react for 12.5 h, and finally raise the temperature to 154 °C under vacuum conditions and hold for 40 min to obtain fluorinated polysiloxane.
[0033] Among them:
[0034] During the preparation of the fluorinated polysiloxane, the stirring speed is controlled at 500 r / min.
[0035] The molar ratio of tetradecamethylcycloheptasiloxane to (3,3,3-trifluoropropyl)trimethoxysilane is 1:0.34.
[0036] The mass of divinyltriaminopropyltrimethoxysilane accounts for 0.7% of the mass of tetradecamethylcycloheptasiloxane.
[0037] The mass of tetraethylammonium hydroxide accounts for 0.8% of the total mass of tetradecamethylcycloheptasiloxane, (3,3,3-trifluoropropyl)trimethoxysilane, divinyltriaminopropyltrimethoxysilane, and tetraethylammonium hydroxide.
[0038] The hydroxyl value of the diethylene glycol adipate in Component A is 125 mgKOH / g, the molecular weight is 900, the manufacturer is Olyron (Jining) Chemical Co., Ltd., and the model is XCP-900D.
[0039] The functionality of the amino-terminated polyether in Component B is 2, the molecular weight is 2000, the manufacturer is Zibo Zhengda Polyurethane Co., Ltd., and the model is ZD-1200.
[0040] The preparation method of the fluorosilicon-modified polyurea anticorrosive coating described in Example 1 consists of the following steps:
[0041] (1) Preparation of Component A
[0042] Put hexamethylene diisocyanate and diphenylmethane diisocyanate into a reaction kettle and heat up to 84 °C. Dropwise add fluorinated polysiloxane into the reaction kettle and react for 1.8 h. Then heat up to 103 °C, dropwise add dehydrated polyethylene adipate glycol ester, and keep the temperature for 3 h. After the reaction is completed, cool to room temperature to prepare Component A;
[0043] (2)Preparation of Component B
[0044] Put N,N-dihydroxy(diisopropyl)aniline and 4,4'-methylene-bis(3-chloro-2,6-diethylaniline) into a reaction kettle, heat up to 94 °C to dissolve them, then add terminal amino polyether and 3,5-bis(trifluoromethyl)phenyl silicone oil, stir at a rate of 450 r / min for 45 min to mix evenly, and finally heat up to 109 °C and react for 2.5 h. After the reaction is completed, cool to room temperature under a nitrogen atmosphere to prepare Component B;
[0045] (3)Preparation of fluorosilicon-modified polyurea anticorrosive coating
[0046] During use, mix Component A and Component B according to a volume ratio of 1:1 and spray them to prepare the fluorosilicon-modified polyurea anticorrosive coating.
[0047] Among them:
[0048] The dehydrated polyethylene adipate glycol ester described in step (1) is obtained by dehydrating polyethylene adipate glycol ester at 111 °C for 3 h.
[0049] Example 2
[0050] The fluorosilicon-modified polyurea anticorrosive coating described in this Example 2 is composed of Component A and Component B, and the volume ratio of Component A to Component B is 1:1. Among them, Component A is composed of the following raw materials by weight: 15 parts of fluorinated polysiloxane, 50 parts of hexamethylene diisocyanate, 21 parts of diphenylmethane diisocyanate, and 36 parts of polyethylene adipate glycol ester; Component B is composed of the following raw materials by weight: 42 parts of terminal amino polyether, 17 parts of 4,4'-methylene-bis(3-chloro-2,6-diethylaniline), 8 parts of N,N-dihydroxy(diisopropyl)aniline, and 7 parts of 3,5-bis(trifluoromethyl)phenyl silicone oil; The preparation method of the fluorinated polysiloxane is as follows: under a nitrogen atmosphere, add tetradecamethylcycloheptasiloxane and tetraethylammonium hydroxide into a reaction vessel, and then dropwise add (3,3,3-trifluoropropyl)trimethoxysilane and divinyltriaminopropyltrimethoxysilane. First, heat up to 75 °C and react for 2.2 h, then heat up to 105 °C and react for 12.5 h, and finally heat up to 155 °C under vacuum conditions and keep it for 40 min to prepare the fluorinated polysiloxane.
[0051] Among them:
[0052] During the preparation of fluorinated polysiloxane, the stirring speed is controlled at 500 r / min.
[0053] The molar ratio of tetradecamethylcycloheptasiloxane to (3,3,3-trifluoropropyl)trimethoxysilane is 1:0.35.
[0054] The mass of diethylenetriaminepropyltrimethoxysilane accounts for 0.8% of the mass of tetradecamethylcycloheptasiloxane.
[0055] The mass of tetraethylammonium hydroxide accounts for 0.8% of the total mass of tetradecamethylcycloheptasiloxane, (3,3,3-trifluoropropyl)trimethoxysilane, diethylenetriaminepropyltrimethoxysilane and tetraethylammonium hydroxide.
[0056] The hydroxyl value of the polyethylene adipate glycol ester in component A is 125 mgKOH / g, the molecular weight is 900, the manufacturer is Oriented (Jining) Chemical Co., Ltd., and the model is XCP-900D.
[0057] The functionality of the terminal amino polyether in component B is 2, the molecular weight is 2000, the manufacturer is Zibo Zhengda Polyurethane Co., Ltd., and the model is ZD-1200.
[0058] The preparation method of the fluorosilicon-modified polyurea anticorrosive coating described in Example 2 consists of the following steps:
[0059] (1) Preparation of component A
[0060] Put hexamethylene diisocyanate and diphenylmethane diisocyanate into the reaction kettle and heat up to 83 °C. Dropwise add fluorinated polysiloxane to the reaction kettle and react for 1.8 h, then heat up to 100 °C and dropwise add dehydrated polyethylene adipate glycol ester and keep it warm for 3 h. After the reaction is completed, cool to room temperature to prepare component A;
[0061] (2) Preparation of component B
[0062] Put N,N-dihydroxy(diisopropyl)aniline and 4,4'-methylene-bis(3-chloro-2,6-diethylaniline) into the reaction kettle, heat up to 95 °C to dissolve them, then add terminal amino polyether and 3,5-bis(trifluoromethyl)phenyl silicone oil, stir at a rate of 400 r / min for 45 min to mix them evenly, and finally heat up to 108 °C and react for 2.5 h. After the reaction is completed, cool to room temperature under a nitrogen atmosphere to prepare component B;
[0063] (3) Preparation of fluorosilicon-modified polyurea anticorrosive coating
[0064] During use, mix component A and component B according to a volume ratio of 1:1 and spray them to prepare the fluorosilicon-modified polyurea anticorrosive coating.
[0065] Among them:
[0066] The dehydrated polyethylene glycol adipate described in step (1) is obtained by dehydrating polyethylene glycol adipate at 110 °C for 3 h.
[0067] Example 3
[0068] The fluorosilicon-modified polyurea anticorrosive coating described in this Example 3 is composed of component A and component B, and the volume ratio of component A to component B is 1:1. Among them, component A is composed of the following raw materials by weight: 17 parts of fluorinated polysiloxane, 48 parts of hexamethylene diisocyanate, 23 parts of diphenylmethane diisocyanate, and 38 parts of polyethylene glycol adipate; component B is composed of the following raw materials by weight: 44 parts of amino-terminated polyether, 15 parts of 4,4'-methylene-bis(3-chloro-2,6-diethylaniline), 10 parts of N,N-dihydroxy(diisopropyl)aniline, and 5 parts of 3,5-bis(trifluoromethyl)phenyl silicone oil; the preparation method of the fluorinated polysiloxane is as follows: under a nitrogen atmosphere, octamethylcyclotetrasiloxane and tetraethylammonium hydroxide are added to a reaction vessel, and then (3,3,3-trifluoropropyl)trimethoxysilane and diethylenetriaminepropyltrimethoxysilane are added dropwise in sequence. First, the temperature is raised to 70 °C and reacted for 2.2 h, then the temperature is raised to 103 °C and reacted for 12.5 h, and finally, under vacuum conditions, the temperature is raised to 153 °C and maintained for 40 min to obtain fluorinated polysiloxane.
[0069] Among them:
[0070] During the preparation process of the fluorinated polysiloxane, the stirring speed is controlled at 500 r / min.
[0071] The molar ratio of octamethylcyclotetrasiloxane to (3,3,3-trifluoropropyl)trimethoxysilane is 1:0.33.
[0072] The mass of diethylenetriaminepropyltrimethoxysilane accounts for 0.6% of the mass of octamethylcyclotetrasiloxane.
[0073] The mass of tetraethylammonium hydroxide accounts for 0.8% of the total mass of octamethylcyclotetrasiloxane, (3,3,3-trifluoropropyl)trimethoxysilane, diethylenetriaminepropyltrimethoxysilane, and tetraethylammonium hydroxide.
[0074] The hydroxyl value of the polyethylene glycol adipate in component A is 125 mgKOH / g, the molecular weight is 900, the manufacturer is Aolilon (Jining) Chemical Co., Ltd., and the model is XCP-900D.
[0075] The functionality of the amino-terminated polyether in component B is 2, the molecular weight is 2000, the manufacturer is Zibo Zhengda Polyurethane Co., Ltd., and the model is ZD-1200.
[0076] The preparation method of the fluorosilicon-modified polyurea anticorrosive coating described in this Example 3 consists of the following steps:
[0077] (1) Preparation of Component A
[0078] Put hexamethylene diisocyanate and diphenylmethane diisocyanate into a reaction kettle and heat up to 85°C. Dropwise add fluorinated polysiloxane to the reaction kettle and react for 1.8 h, then heat up to 105°C and dropwise add dehydrated poly(ethylene glycol adipate) and keep it warm for 3 h. After the reaction is completed, cool it to room temperature to obtain Component A;
[0079] (2) Preparation of Component B
[0080] Put N,N-dihydroxy(diisopropyl)aniline and 4,4'-methylene-bis(3-chloro-2,6-diethylaniline) into a reaction kettle, heat up to 93°C to dissolve them, then add terminal amino polyether and 3,5-bis(trifluoromethyl)phenyl silicone oil, stir at a rate of 500 r / min for 45 min to mix them evenly, and finally heat up to 110°C and react for 2.5 h. After the reaction is completed, cool it to room temperature under a nitrogen atmosphere to obtain Component B;
[0081] (3) Preparation of the fluorosilicon-modified polyurea anticorrosive coating
[0082] During use, mix Component A and Component B according to a volume ratio of 1:1 and spray them to obtain the fluorosilicon-modified polyurea anticorrosive coating.
[0083] Among them:
[0084] The dehydrated poly(ethylene glycol adipate) described in step (1) is obtained by dehydrating poly(ethylene glycol adipate) at 113°C for 3 h.
[0085] Comparative Example 1
[0086] The preparation method of the fluorosilicon-modified polyurea anticorrosive coating described in this Comparative Example 1 is the same as that in Example 1. The only difference is that its raw material composition is different. In Component A of the fluorosilicon-modified polyurea anticorrosive coating described in this Comparative Example 1, fluorinated polysiloxane is no longer added, and the other raw materials are the same as those in Example 1.
[0087] Perform performance tests on the fluorosilicon-modified polyurea anticorrosive coatings prepared in Examples 1-3 and Comparative Example 1. Under the conditions of a temperature of 25 °C and a relative air humidity of 55%, using 304 steel as the substrate, spray the polyurea anticorrosive coatings prepared in Examples 1-3 and Comparative Example 1 on it, and conduct performance tests after curing for 7 days. Among them, the tensile strength is tested in accordance with GB / T 2567-2021; the tear strength is tested in accordance with GB / T 529-2008; the adhesion is tested by the pull-off method in accordance with GB / T 5210-2006; the neutral salt spray resistance is tested in accordance with GB / T 1771-2007, and the resistance to 5 wt% NaCl solution, 5 wt% NaOH solution, and 5 wt% H2SO4 solution is tested in accordance with GB / T 9274-1988. The oil resistance test is to immerse the specimen in 0 # diesel oil for 30 days and then test its tensile strength; the results are shown in Table 1 below:
[0088] Table 1 Performance test results of the polyurea anticorrosive coatings prepared in Examples 1-3 and Comparative Example 1
[0089]
Claims
1. A fluorosilicon-modified polyurea anti-corrosion coating, characterized in that: It consists of component A and component B, and the volume ratio of component A to component B is 1:
1. Among them, component A, calculated by weight parts, consists of the following raw materials: 15 - 17 parts of fluorinated polysiloxane, 48 - 50 parts of hexamethylene diisocyanate, 21 - 23 parts of diphenylmethane diisocyanate, and 36 - 38 parts of diethylene glycol adipate; Component B, calculated by weight parts, consists of the following raw materials: 42 - 44 parts of terminal amino polyether, 15 - 17 parts of 4,4'-methylene-bis(3-chloro-2,6-diethylaniline), 8 - 10 parts of N,N-dihydroxy(diisopropyl)aniline, and 5 - 7 parts of 3,5-bis(trifluoromethyl)phenyl silicone oil; The preparation method of the fluorinated polysiloxane is as follows: Under a nitrogen atmosphere, octamethylcyclotetrasiloxane and tetraethylammonium hydroxide are added to a reaction vessel, and then (3,3,3-trifluoropropyl)trimethoxysilane and divinyltriaminopropyltrimethoxysilane are added dropwise in sequence. First, the temperature is raised to 70 - 75°C and reacted for 2.2 h, then the temperature is raised to 103 - 105°C and reacted for 12.5 h, and finally, under vacuum conditions, the temperature is raised to 153 - 155°C and maintained for 40 min to prepare the fluorinated polysiloxane; Wherein: The molar ratio of octamethylcyclotetrasiloxane to (3,3,3-trifluoropropyl)trimethoxysilane is 1:0.33 - 0.35; The mass of divinyltriaminopropyltrimethoxysilane accounts for 0.6 - 0.8% of the mass of octamethylcyclotetrasiloxane; The mass of tetraethylammonium hydroxide accounts for 0.8% of the sum of the masses of octamethylcyclotetrasiloxane, (3,3,3-trifluoropropyl)trimethoxysilane, divinyltriaminopropyltrimethoxysilane, and tetraethylammonium hydroxide.
2. The fluorosilicon-modified polyurea anticorrosive coating according to claim 1, wherein: During the preparation of the fluorinated polysiloxane, the stirring speed is controlled at 500 r / min.
3. The fluorosilicon-modified polyurea anticorrosive coating according to claim 1, wherein: The hydroxyl value of the diethylene glycol adipate in component A is 125 mgKOH / g, and the molecular weight is 900.
4. The fluorosilicon-modified polyurea anticorrosive coating according to claim 1, wherein: The functionality of the terminal amino polyether in component B is 2, and the molecular weight is 2000.
5. A method for preparing the fluorosilicon-modified polyurea anticorrosive coating according to claim 1, characterized in that: It consists of the following steps: (1)Preparation of component A Put hexamethylene diisocyanate and diphenylmethane diisocyanate into a reaction kettle and heat up to 83 - 85°C. Dropwise add fluorinated polysiloxane to the reaction kettle and react for 1.8 h, then heat up to 100 - 105°C, dropwise add dehydrated diethylene glycol adipate and keep warm for 3 h. After the reaction is completed, cool to room temperature to prepare component A; (2)Preparation of component B Put N,N-dihydroxy(diisopropyl)aniline and 4,4'-methylene-bis(3-chloro-2,6-diethylaniline) into a reaction kettle, heat up to 93 - 95°C to dissolve them, then add terminal amino polyether and 3,5-bis(trifluoromethyl)phenyl silicone oil, stir at a rate of 400 - 500 r / min for 45 min to mix evenly, and finally heat up to 108 - 110°C and react for 2.5 h. After the reaction is completed, cool to room temperature under a nitrogen atmosphere to prepare component B; (3)Preparation of fluorosilicon-modified polyurea anticorrosive coating During use, mix component A and component B according to a volume ratio of 1:1 and spray them to prepare the fluorosilicon-modified polyurea anticorrosive coating.
6. The preparation method of the fluorosilicon-modified polyurea anticorrosive coating according to claim 5, characterized in that: The dehydrated polyethylene glycol adipate described in step (1) is obtained by dehydrating polyethylene glycol adipate at 110 - 113°C for 3 hours.
Citation Information
Patent Citations
Special dirt-resistant organosilicone oligomer for polyurea and preparation method thereof
CN103804689A
Polyureas copolymer with main chain containing siloxane composition unit and preparation method thereof
CN103834034A
Easily-processed polyurethane elastomer and preparation method thereof
CN115093539A
High-performance water-based asphalt waterproof coating and preparation method thereof
CN116376367A